Measuring cost effectiveness of product wheels in food manufacturing - Jensen, Emilie (Kansas State University, 2014)
The focus of this research is to create a production schedule that will increase capacity while staying within business constraints of shelf life and warehouse space in a industrial food processing environment. The results support that product wheels maximize process responsiveness by lengthening production runs, and increasing safety stock inventory. In doing so, it maintains acceptable customer service levels and minimizes overtime costs. This study develops a model that simulates the relevant variables impacting the performance of the operation. The results show significant cost reductions are achieved by eliminating changeovers, increasing line capacity, safety stock levels protect against 99% of order variation, and warehouse space is available to house increased cycle stock and safety stock. Given the results on this line, I recommend expanding the model to other food processing locations within the business to further increase capacity and decrease overtime expenses.
Keywords: Product wheels; Inventory; Order fulfillment